Evaluation of signal transducer and activator of transcription 3 (STAT-3) protein expression in non-hodgkin lymphoma cases in Hospital Universiti Sains Malaysia - Muhamad, Izyan Rifhana (2023)
Background: Evolving targeted therapy on Janus Associated Kinase-Signal Transducer and Activator of Transcription (JAK-STAT) signalling pathway especially pertaining to STAT-3 protein in non-Hodgkin lymphoma (NHL), provide new treatment strategies. STAT-3 protein also related to prognostication of NHL. Hence, we aimed to evaluate the expression of STAT-3 protein in NHL cases, diagnosed in Hospital Universiti Sains Malaysia. Methods: A retrospective cross sectional study using formalin fixed paraffin embedded tissue blocks of 95 NHL cases were obtained. STAT-3 immunostaining was performed and evaluated. The association between clinicopathological characteristics and STAT-3 protein expression was analysed using the Pearson chi-square and Fisher’s exact test. A p-value of < 0.05 is considered statistically significant. Results: Majority of the cases (78.9 %) have positive STAT-3 protein expression. 64.2 % were among aggressive B cell NHL whilst 20 % of them are Diffuse Large B Cell Lymphoma, non-germinal centre B subtype (DLBCL-NGCB). There is significant association between STAT-3 protein expression with DLBCL subtypes (p = 0.046). Conclusion: STAT-3 protein was significantly associated with DLBCL, one of the aggressive B cell lymphoma subtypes. It could be one of the possible markers to prognosis in NHL. However, a more extensive study with a combination of JAK protein needs to be done in the future to elucidate the mechanism of the JAK-STAT pathway in NHL and its associated role.